Diseño de un plan de negocios de producción, exportación y comercialización de limonada de panela en Japón (2021)
This research includes the design of a business plan for panela's lemonade production in Colombia, in order to export and market this product in Japan, taking into account the business opportunities in this Asian country. The above is generated thanks to the high export of citrus beverages that Japan gives, for having a production of citrus beverages that is not enough to supply its population, therefore, Colombia, being the sixteenth (16th) lemon's producer worldwide, the second world panela's producer, and by producing a citrus drink such as panela's lemonade, it has a competitive advantage to enter the Japanese market, which would generate an expansion of panela's lemonade exports and an increase in the sugarcane's exploitation, resulting in a boost to the national economy and the opening of a new market for Colombian's companies.